Gamification of Electronic Negotiation Training - Schmid, Andreas (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2022)
Organisations are involved in various types of negotiation. As digitalisation advances, such business negotiations are to a large extent electronic negotiations. Consequently, dedicated training for such electronic negotiations is important for mastering negotiation skills. The present book develops a new approach for a motivating and improved e-negotiation training by applying gamification, i.e. using game design elements in a non-game context, in order to improve participants' motivation, engagement, and learning outcomes. A negotiation support system used within an e-negotiation training is enhanced with game design elements. The book describes the design process, its theoretical foundations, and the evaluation of the gamified negotiation support system. The final quantitative evaluation shows higher motivation, engagement and better learning outcomes for participants in the gamified training compared to a conventional training. Organisations can employ the designed artefact for fundamental and effective e-negotiation training. Additionally, the book provides insights in how to design a gamified system for a particular application context. About the author Andreas Schmid was a research assistant at the Information Systems Department 1 - Organisational Communication at the University of Hohenheim, Germany, and is currently working as an IT specialist. His research interests include gamification, e-learning, negotiations, and software development.
Introduction -- Theoretical Background -- Design Science Research Methodology -- A Framework for Gamified Electronic Negotiation Training -- Gamifying Electronic Negotiation Training - A Mixed Method Study of Students' Motivation, Engagement and Learning -- Rankings or Absolute Feedback? Investigating Two Feedback Alternatives for Negotiation Agreements in a Gamified Electronic Negotiation Training -- Gamification of Electronic Negotiation Training: Effects on Motivation, Behaviour and Learning -- Discussion & Outlook.
Keywords: Technological innovations; Business information services; Innovation and Technology Management; IT in Business